2011
DOI: 10.1136/ip.2010.029835
|View full text |Cite
|
Sign up to set email alerts
|

Booster seat legislation: does it work for all children?

Abstract: Racial/ethnic minority groups and those of lower socioeconomic status have significantly lower use and proper use of booster seats. Legislation may increase the total use of booster seats but not necessarily the correct use of the restraint, particularly in racial/ethnic minorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Although the magnitude of difference has shifted and methods vary, our findings are consistent with the published literature. [20][21][22]32 In 2004, 28% of black 4-to 8-year-olds at a child restraint system inspection program were not appropriately restrained compared with 12% of whites. 20 Surveys of insured drivers of children involved in a sample of crashes in 2000-2004 revealed more suboptimal restraint use among African American 1-to 3-year-olds and 4-to 8-year-olds than whites (8% vs 4% and 76% vs 64%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the magnitude of difference has shifted and methods vary, our findings are consistent with the published literature. [20][21][22]32 In 2004, 28% of black 4-to 8-year-olds at a child restraint system inspection program were not appropriately restrained compared with 12% of whites. 20 Surveys of insured drivers of children involved in a sample of crashes in 2000-2004 revealed more suboptimal restraint use among African American 1-to 3-year-olds and 4-to 8-year-olds than whites (8% vs 4% and 76% vs 64%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…7,9,10 Although child passenger safety practices in the United States have improved over time, [11][12][13] premature transitions to booster seats and seat belts persist, [13][14][15][16][17][18] and racial disparities exist. 8,17,[19][20][21][22][23] Minority children have higher directly observed rates of both being inappropriately restrained 8,[20][21][22] and unrestrained 8,17,19,20 compared with white children. Driver minority race/ethnicity, lower education, and lower household income are associated with driver-reported suboptimal restraint use among children ,9 years old who have been involved in an MVC.…”
mentioning
confidence: 99%
“…However, recent research suggests that though CRS legislation may increase overall CRS use, it does not necessarily increase the correct CRS use. For example, Brixey et al (2011) recently observed booster seat use among 4-to 7-year-old children in the state of Wisconsin before and after the introduction of legislation mandating booster seat use. Though overall use of booster seats increased following introduction of the legislation (from 24% to 43%), only limited improvements in correct booster seat use were observed (from 21% to 28%).…”
Section: Crs Legislation Effectivenessmentioning
confidence: 97%
“…As noted recently by Bilston et al (2011) andBrixey et al (2011), CRS legislation should be accompanied by a culturally appropriate, multifaceted community-based education campaign in order to realize the CRS's full injury reduction potential. Indeed, Ebel et al (2003) demonstrated significant increases in the use of booster seats for children aged 4 to 8 years following a multifaceted community education campaign in King County, Washington.…”
Section: Misuse and Crs Legislationmentioning
confidence: 98%
“…9 Similarly, graduated driver licensing systems have been shown to reduce motor vehicle collision rates in teenagers. One such law in Connecticut demonstrated a 40% reduction in motor vehicle collision rates for 16-year-olds, 30% for 17-year-olds, 16% for 18-year-olds, and 7% for 19-year-olds.…”
Section: Precedent For Legislative Interventionmentioning
confidence: 99%